Přínos využití automatizované obsahové analýzy ve foresightu - Kováříková, Ludmila; Grosová, Stanislava (Vysoké učení technické v Brně, Fakulta podnikatelská, 2014)
Purpose of the article: The present manuscript summarizes benefits of the use of computer-based content analysis in a generation phase of foresight initiatives. Possible advantages, disadvantages and limitations of the content analysis for the foresight projects are discussed as well. Methodology/methods: In order to specify the benefits and identify the limitations of the content analysis within the foresight, results of the generation phase of a particular foresight project performed without and subsequently with the use of computer based content analysis tool were compared by two proposed measurements. Scientific aim: The generation phase of the foresight is the most demanding part in terms of analysis duration, costs and resources due to a significant amount of reviewed text. In addition, the conclusions of the foresight evaluation are dependent on personal views and perceptions of the foresight analysts as the evaluation is based merely on reading. The content analysis may partially or even fully replace the reading and provide an important benchmark. Findings: The use of computer based content analysis tool significantly reduced time to conduct the foresight generation phase. The content analysis tool showed very similar results as compared to the evaluation performed by the standard reading. Only ten % of results were not revealed by the use of content analysis tool. On the other hand, several new topics were identified by means of content analysis tool that were missed by the reading. Conclusions: The results of two measurements should be subjected to further testing within more foresight projects to validate them. The computer based content analysis tool provides valuable benchmark to the foresight analysts and partially substitute the reading. However, a complete replacement of the reading is not recommended, as deep understanding to weak signals interpretation is essential for the foresight.
Benefits of Computer Based Content Analysis to Foresight
Keywords: foresight; content analysis; horizon scanning; weak signal; foresight generation phase